(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the lexical semantic challenges encountered in the translation process, examining the complex relationship between word meanings across different linguistic and cultural systems. The research analyzes how translators navigate issues of polysemy, semantic fields, connotative meanings, and cultural-specific lexical items when transferring content between languages. Through examination of both theoretical frameworks and practical translation cases, this study identifies key lexical semantic problems that affect translation quality, including issues of equivalence, contextual meaning, and the translation of culture-bound expressions, idioms, and metaphors.